Assessing the consistency of flammability indices across field and laboratory experimental tests for some Moroccan forest fuels - Salaheddine Essaghi; M’hamed Hachmi; Sabrine Laajali; Mohamed Chikhaoui; Allal Hamouda (PLoS ONE, 2026)
Flammability is evaluated differently depending on the plant level (whole plant, shoot, twig) and the scale of fire experiments (field versus laboratory). Inaccuracies in fire risk prediction highlight a standardisation problem, which requires comparing the flammability of the same individuals tested through contrasting experimental tests. The samples were collected from a forest site known for its high fire recurrence. Five Mediterranean tree and shrub species were tested in both laboratory and field-scale experiments, selected from the most commonly used methods, and conducted at the twig and shoot levels, respectively. In both tests, Pinus canariensis proved to be the most flammable species, while Quercus suber and Cistus salviifolius ranked second and fourth in flammability. The third position was taken by Arbutus unedo for shoot flammability and by Pistacia lentiscus for twig flammability. However, the shoot flammability test stood out because of its distinction between the moderately flammable group of species ( Q. suber , A. unedo and C. salviifolius ) and the least flammable group ( P. lentiscus ), that were all less flammable than P. canariensis , unlike the twig test. These findings could improve the understanding of researchers and forest managers regarding plant flammability, regardless of the test or device used, provided technical resources are available, at least in the study site for the five species examined. Additional tests involving a broader range of plant species are essential for a reliable comparison of the flammability assessments examined. Further methods of flammability assessment are needed to interpret empirical rankings, especially when translating laboratory results into predictive indicators of wildfire behaviour in natural ecosystems.